2008
DOI: 10.1111/j.1750-3841.2008.00891.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Grain Type and Toasting Conditions of Barrels on the Concentration of the Volatile Substances Released by the Wood and on the Sensory Characteristics of Montepulciano d'Abruzzo

Abstract: We report the results of an aging trial of Montepulciano d'Abruzzo D.O.C. wine in commercially available oak barrels that differed in the type of wood grain (extra fine and fine) and cooperage toasting conditions: medium (EVM), light (EVL), medium for a shorter time (CM), and, finally, a single short-time pretoasting stage at high temperature (ExpT). The chemical-physical composition, the volatile substances released by the wood, and the sensory characteristics of wines after 6 and 12 mo of aging were monitore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 12 publications
(7 reference statements)
0
14
0
1
Order By: Relevance
“…Meanwhile, oxidation, condensation, hydrolysis, and esterification also happen during the wine aging process, potentially resulting in the formation of many new volatile compounds, and these compounds can improve the aromatic complexity of wine [ 31 ]. It is known that oak barrel type and toasting level are two important factors that impact wine aging performance [ 32 , 33 ]. It has been reported that a short aging process can release the limited volatiles from the oak barrel to the wine matrix, which does not effectively improve wine aging features.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, oxidation, condensation, hydrolysis, and esterification also happen during the wine aging process, potentially resulting in the formation of many new volatile compounds, and these compounds can improve the aromatic complexity of wine [ 31 ]. It is known that oak barrel type and toasting level are two important factors that impact wine aging performance [ 32 , 33 ]. It has been reported that a short aging process can release the limited volatiles from the oak barrel to the wine matrix, which does not effectively improve wine aging features.…”
Section: Introductionmentioning
confidence: 99%
“…This may be explained by the increase in complexity and the differences in concentrations of the volatile components, particularly esters . Previous studies have highlighted that the increase in toasting process led to an accentuation of the perception of woody, vegetative, caramel, spicy, coconut, and smoky notes. , Some authors also observed a significant negative correlation between the presence of oak wood and the perception of fruity notes in various red wines…”
Section: Resultsmentioning
confidence: 94%
“…The method proposed by Bosso et al, 2008 was used, but with the following changes: 1-heptanol (250 μL of 54.73 mg/L) and 3,4-dimetylphenol (250 μL of 50 mg/L) were added as internal standards to 25 mL of wine, then water was added to reduce the concentration of alcohol to less than 5 %. SPE cartridges were activated with 5 mL of dichloromethane, 5 mL of methanol and 5 mL of ultrapure water in succession without drying the cartridges between each passage.…”
Section: Volatile Compound Analysismentioning
confidence: 99%
“…Oenological results are influenced by a wide variety of factors, such as size of chips, infusion time, toasting degree, wood type and the wine's extractive capacity. Similarly, traditional refinement in wooden containers can give different results depending on factors, such as contact time of the wine, the use of new or used barrels, the period and frequency of any batonnage, and the possibility of using containers of different sizes (barriques, tonneaux and larger barrels) (Bosso et al, 2008;Gutiérrez Afonso, 2002;Ortega-Heras et al, 2010). Therefore, discriminating wines that have been obtained using one refinement technique instead of another is particularly challenging due to the multiplicity of variables involved.…”
Section: Introductionmentioning
confidence: 99%